Optimalisasi Kesehatan Masyarakat melalui Pembinaan Dasar Olahraga Pendidikan Jasmani Berkelanjutan bagi Masyarakat - Amrizal Amrizal (Jurnal Kabar Masyarakat, 2025)
Physical education and sport are long-term investments in improving the quality of human resources. In this context, physical education not only plays a role in developing physical skills, but also in the cognitive and affective aspects of learners, all of which contribute to character building and healthy lifestyles. These methods are: inductive method and deductive method. The results of the research on “Optimizing Public Health Through Basic Sports Development of Sustainable Physical Education for the Community” show a significant positive impact on the physical and mental health of the community. Structured and sustainable sports programs, such as fitness exercises, have proven effective in improving the quality of life and well-being of residents. The program succeeded in raising community awareness about the importance of maintaining health through exercise. The education provided during the program helped participants understand the benefits of a healthy lifestyle and encouraged them to adopt new, healthier habits.